IMPLEMENTATION OF STATE PROPERTY MANAGEMENT POLICY AT THE SECRETARIAT GENERAL OF THE GENERAL ELECTION SUPERVISORY AGENCY REPUBLIC OF INDONESIA - Ahmad Hidayat; Fahdrian Kemala (International Peneliti Ekonomi, Sosial dan Teknologi, 2022)
Implementation of policies on the management of state goods at the Secretariat General of the General Elections Supervisory Agency of the Republic of Indonesia. The purpose of this study was to determine and evaluate the implementation of policies on the management of state property in the General Secretariat of the General Elections Supervisory Agency. The theory used as a reference is the theory of George C. Edward III which states that there are four things that affect the implementation of policies, namely communication, resources, disposition and structure of the bureaucracy. This study uses a qualitative method with eleven informants consisting of officials/employees in the Secretariat General of the General Elections Supervisory Agency and the Provincial General Elections Supervisory Agency, officials within the Ministry of Finance and members of the working group of the Government Accounting Standards Committee. Based on the results of the research, it is known that the implementation of the policy on the management of state property within the Secretariat General of the General Elections Supervisory Agency has not gone well. The factors that influence the implementation of the policy are communication, resources, disposition and bureaucratic structure. The inhibiting factors are resources, disposition and bureaucratic structure, while communication does not become an obstacle in implementing state property management policies at the Secretariat General of the General Elections Supervisory Agency.